Anti-neuroinflammatory asarone derivatives from the rhizomes of Acorus tatarinowii. Issue 14 (26th January 2017) - Qin, Da-Peng; Feng, Xiao-Lin; Zhang, Wei-Yang; Gao, Hao; Cheng, Xiao-Rui; Zhou, Wen-Xia; Yu, Yang; Yao, Xin-Sheng
Abstract : A novel 7- O -7′ type mesomeric neolignan, meso -asarolignan A (1 ), six pairs of new neolignan enantiomers, (±)-asarolignan B–G (2a/2b, 3a/3b, 4–6, 7a/7b ), along with 16 known analogues (8–23 ) were isolated from the rhizomes of Acorus tatarinowii . Abstract : A novel 7- O -7′ type mesomeric neolignan, meso -asarolignan A (1 ), six pairs of new neolignan enantiomers, (±)-asarolignan B–G (2a/2b, 3a/3b, 4–6, 7a/7b ), along with 16 known analogues (8–23 ) were isolated from the rhizomes of Acorus tatarinowii . The structures of the new compounds were elucidated by extensive analysis of spectroscopic, X-ray diffraction, and computational data. Compounds1–3 represent rare examples of naturally occurring lignans with a 7- O -7′ linkage pattern. All isolated compounds were assayed for their anti-neuroinflammatory effects on tumor necrosis factor α (TNF-α) production in an activated murine microglia cell line. Compounds7(a/b), 14(a/b), 16, 20, and22 reduced TNF-α levels without high cell toxicity in LPS-activated BV-2 cells.